The emergence of convergence clubs among Greek regions - Panagiotis Artelaris; Dimitris Kallioras; George Petrakos (European Regional Science Association (ERSA), 2010)
The evaluation of regional inequalities and the monitoring of their evolution (regional convergence/divergence analysis) is an issue of extreme interest in the field of regional science as it demonstrates the role of market dynamics and appraises the effectiveness of regional policy. Extending the methodology of (regional) convergence clubs, the paper examines for the existence of convergence clubs, in per capita GDP terms, among the NUTS III regions of Greece during the period 1995 - 2005. The approach of (regional) convergence clubs relies on recent paradigms of economic growth and indicates the existence of (regional) convergence within (regional) convergence clubs without the precondition of (regional) convergence between those clubs. The findings of the paper do not verify the existence of regional convergence clubs in Greece. In contrast, they reveal clear trends of divergence, (identifying, additionally, sub-clubs of divergence) stressing out the underestimation of the country's regional problem.
Keywords: R11; R12; R15; 330; regional convergence clubs; Greek regions